A Long Walk for Nothing? ASEAN’s Ineffectivity in Combating Transnational Organized Crime: the Case of Drug Trafficking in the ‘Golden Triangle’ - Nauvarian, Demas; Pramudia, Putu Shangrina (Universitas Sebelas Maret, 2022)
This paper seeks to analyze ASEAN’s ineffectivity in combating transnational organized crime, with special focus on the case of drug trafficking. With most member states being in a developing economy state, the region of Southeast Asia become a target for the various activities of transnational organized crimes (TOCs). One of the prominent TOC operating in the region is illegal drug trafficking, with its center in the region being at the Golden Triangle area—an intersection between Myanmar, Laos, and Thailand. The three countries themselves are known for being production points of illegal drugs, with little national effort to combat it. While the hope for regional action from ASEAN emerge, ASEAN’s various effort in combating illegal drug trafficking seems to be ineffective. This is evidenced by the constant increase of illegal drug production and distribution in the region and even outwards. This paper seeks to explain this ineffectivity. By utilizing the framework of security community, this paper argues that there is a lack of collective identity and community sense that become the underlying factor for this ineffectivity. Therefore, this paper concludes the need of ideational shift to increase effectivity in ASEAN’s effort.